Gene Expression Profiles for Macrophage in Tissues in Response to Different Exercise Training Protocols in Senescence Mice - Uchida, Masataka; Horii, Naoki; Hasegawa, Natsuki; Fujie, Shumpei; Oyanagi, Eri; Yano, Hiromi; Iemitsu, Motoyuki (Frontiers in Sports and Active Living, 2019)
Age-induced chronic inflammation is prevented by aerobic and resistance exercise training. However, the effects of the mechanism of exercise on chronic inflammation in each tissue remains unclear. The aim of this study was to investigate the effects of resistance and aerobic training on gene expression profiles for macrophage infiltration and polarization (M1/M2 ratio) with chronic inflammation in various tissues of aged model mice. Male 38-week-old SAMP1 (senescence-accelerated prone mouse 1) mice were randomly divided into three groups—sedentary (Aged-Sed-SAMP1), aerobic training (Aged-AT-SAMP1; voluntary running), and resistance training—for 12 weeks (Aged-RT-SAMP1; climbing ladder). Resistance and aerobic exercise training prevented an increase in circulating TNF-α levels (a marker of systemic inflammation) in aged SAMP1 mice, along with decreases in tissue inflammatory cytokine (TNF-α and IL-1β) mRNA expression in the heart, liver, small intestine, brain, aorta, adipose, and skeletal muscle, but it did not change the levels in the lung, spleen, and large intestine. Moreover, resistance and aerobic exercise training attenuated increases in F4/80 mRNA expression (macrophage infiltration), the ratio of CD11c/CD163 mRNA expression (M1/M2 macrophage polarization), and MCP-1 mRNA expression (chemokine: a regulator of chronic inflammation) in the chronic inflamed tissues of aged SAMP1 mice. These results suggested that resistance and aerobic exercise training-induced changes in gene expression for macrophage infiltration and polarization in various tissues might be involved in the prevention of age-related tissue chronic inflammation, and lead to a reduction of the increase in circulating TNF-α levels, as a marker of systemic inflammation, in aged SAMP1 mice.